2017
DOI: 10.4236/jssm.2017.106040
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Human Risks in Service: A New Model

Abstract: The modeling of a customer experience realized through a service blueprint is useful for visualizing the structures and processes involved in its production. However, the classical service blueprint fails to consider the contribution of human factors-motivation, emotion, satisfaction, etc.-that are essential elements of service interactions and can represent important risks of non-quality. Consequently, we have developed an enhanced service blueprint dedicated to Enterprise Risk Management (ERM), which include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Other authors, such as [4], reported the study of the influence of the human factor on risks in the service sector. For integrated measurement of the risk zone under the dominant action of the human factor, a sociogram of relationships in the group and the concept of modeling production risk management were used.…”
Section: The Object Of This Study Is a Technique To Reduce The Person...mentioning
confidence: 99%
“…Other authors, such as [4], reported the study of the influence of the human factor on risks in the service sector. For integrated measurement of the risk zone under the dominant action of the human factor, a sociogram of relationships in the group and the concept of modeling production risk management were used.…”
Section: The Object Of This Study Is a Technique To Reduce The Person...mentioning
confidence: 99%
“…Pöppel, Finsterwalder, and Laycock [51] reflected changes in the service process resulting from the introduction of digitization in the film industry by modifying the SB component. Barbieri et al [52] considered a sociogram as a human factor dimension to visualize the reception service process of luxury hotels. The proposed SB of this study is rather close to the latter class of redesign approaches as it reorganizes the service encounters based on customer perceptions of the service while employing LDA text analysis in service blueprinting.…”
Section: Service Blueprint Based Redesignmentioning
confidence: 99%